Two “myxomycete diseases” occurred on cultivated fields of Dendrobium candidum - TU Yanla; XIAO Fang; ZHANG Jingze; LU Qiqiang; WANG Lefu (浙江大学学报. 农业与生命科学版, 2016)
Dendrobium Candidum (Orchidaceae) is an aerophyte cultivated widely in Zhejiang Province as traditional Chinese herbal medicine. Two “myxomycete diseases”, which affected the growth of plants, were found in cultivated fields of D. candidum in Yueqing City of Zhejiang Province in 2011. Two “pathogens” were identified as Comatricha pulchella (C. Bab) Rostaf. and Fuligo septica (L.) Wigg. by morphological characters and molecular data, including light microscopy, scanning electron microscopy, spore germination and analysis of 18S rDNA sequences. Sporocarps of C. pulchella were stipitate and gregarious, with about 2.2 mm in total height and cylinder-shaped sporangia, intensively distributed on the plant stem and leaf surface; its dense capillitium arose from the entire columella and dark spores in mass (7.2-8.0 μm in diameter). Whereas, the sporocarp of F. septica was a large scale cushion-shaped or irregular type aethalium, with up to 15 cm in length and the colors of the outer peridium in the spore-bearing stage, which could cover the whole cluster of the plants. White, stipitate and young sporangia were observed on young leaves and stems of D. Candidum after 15 d of inoculation with C. pulchella, and the mature sporangia were observed after 20 d of inoculation. Whereas, no sporocarp was observed on young leaves and stems of D. Candidum, but yellowish sporocarps produced on the substrate near the root after 15 d of inoculation with F. septica; with development of the sporocarp, the color became opalescent, and large sporocarps were observed after 30 d of inoculation, which covered the basal part of stems. The artificial inoculation results showed that both the myxomycetes could not infect the living plants. To the best of our knowledge, the two species both were the new record in Zhejiang Province. The discovery of C. pulchella and F. septica enriches the fungal resources of Zhejiang Province and also provides fundamental materials to further study on geographical distribution and diversity of myxomycete in China.